Toward a Theory of Minority Entrepreneurship in the Non-Profit Arts Sector. - White, Jason C. (Journal of Arts Management, Law & Society, 2018)
Throughout most of the entrepreneurship research literature, the entrepreneur is generally identified as a native-born White male who undertakes either self-employment or firm creation in Western developed countries. In addition, most of the literature frames these entrepreneurial actions as for-profit activities. Perhaps due in part to such prevailing frames, we know little about minority entrepreneurship, let alone as it occurs within the non-profit arts sector. To aid the field in new understandings, I review the minority entrepreneurship literature, identify minority entrepreneurship strategies, make connections to the non-profit arts sector, and propose new directions for theory development in the field.